Beyond literary analysis : teaching students to write with passion and authority about any text - Marchetti, Allison (Portsmouth, New Hampshire : Heinemann, 2018)
Allison Marchetti and Rebekah O'Dell invite you to join them on a transformational journey. Out of the dark tunnel of boring literary analysis assignments, they lead you into a world where students learn to write fresh, compelling, authentic arguments based on their own unique interests. "There is a place for analysis of literature in our classrooms," they write. "But we think there is more. In this book, we invite you to explore your teaching of analytical writing from a new perspective. To open your mind to the real world of analytical writing, and challenge traditional notions about what students should be analyzing and how they should write it." Allison and Rebekah offer a broadened definition of analysis for the 21st century classroom. "Analysis is everywhere," they argue. "It's about video games and athletes' seasons, and the latest album, or the new Netflix series." This new definition of "text" allows students to tap into their passions-and learn to write with expertise on topics that matter to them. "No matter where your students begin as writers-full of confidence or full of avoidance-unleashing them to explore the topics and texts they are passionate about can transform your classroom and transform their writing." With samples throughout the book, you'll see what students of all levels and experiences can do when they're supported with mentor texts, targeted writing instruction, and the opportunity to write beyond literary analysis.
1.Analysis in the wild -- 2.Toward a new understanding of analysis -- 3.The essential tools of analysis -- 4.Exploring passion -- 5.Exploring ideas -- 6.Exploring structure -- 7.Exploring authority -- 8.Movie and and television analysis -- 9.Music analysis -- 10.Sports analysis -- 11.Video game analysis -- 12.Literary analysis -- 13.Gathering your own resources.
Includes bibliographical references and index.
Keywords: CRITICISM -- STUDY AND TEACHING (SECONDARY)